Sistem Informasi Perancangan Pendaftaran Online Berbasis Web Di Puskesmas Pataruman Kabupaten Bandung Barat - Ilham Safril Arrahman; Fahmi Azi Permana (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Puskesmas is a health facility that organizes public health efforts and first-level individual health efforts that always strive to achieve efficiency and effectiveness of services to the community, so it needs a facility and infrastructure that supports data processing of a website-based information system that is useful for providing information quickly and accurately. The system used at the Pataruman Health Center still uses a manual system using paper as a data processing tool so that in the end various problems arise. Such as the difficulty of controlling information on user data, patient data, patient registration, the process of searching for patient data becomes long and inaccurate due to the accumulation of paper containing data, and because of the perishable nature of paper, it is very possible to lose data. This research uses the waterfall method by using Apache 2.4.34 as a web server, PHP 5.6.38 as a programming language and MySQL 5.0.21 as a database. So the author created a website to support the performance of Pataruman Public Health Center, based on the results of research conducted at Pataruman Public Health Center. This website is designed with a simple display to make it easier for health center staff to use it. It can be concluded that this research has succeeded in creating an information system using the website method.